“Do We Care Enough?”- A Critical Analysis of the Legal Duty of Care Contained in the National Environmental Management Act and Its Application to Wetland Restoration (Journal of Wetlands Environmental Management, 2023)
South African wetlands are disappearing at a rapid rate. Considering the vital functions they provide, they require optimal protection and, where appropriate, restoration. In line with protecting and restoring the environment, section 28 of South Africa’s National Environmental Management Act 107/1998 (NEMA) makes provision for the duty of care and remediation of environmental damage (DOC). This enforceable duty rests upon every person (natural and juristic) to, amongst others, prevent pollution or degradation of the environment or to stop, minimise, and rectify such pollution or degradation by taking certain measures. For wetlands, this duty is bound to the idea of 'ecological restoration’ (ER), which is defined as “the process of helping to recover an ecosystem that has been degraded, damaged or destroyed”. This paper, through the selected theoretical framework for ER, sets out the literature to provide the foundation for 1. the international obligation of restoration; and 2. a critical analysis of section 28 of NEMA through the selected ER framework for wetlands ecosystems. The research reveals the gaps in support of the argument that the DOC principle may lack in addressing the full embodiment of ER and providing the consequences of such failure. Thus, calling for the amendment of section 28 of NEMA (DOC) to include the appropriate provisions and the removal of superfluous and confusing provisions such as ‘significant’. However, there is scope for the improvement and development of ER for the 2024 proposed National Joint Wetland Management Policy.